The Effect of Price, Product Quality, and Service Quality on Consumer Satisfaction of Coffee Drink Products at Tilasawa Coffee Roaster - Tafuzi Vaoria; Wulandari Dwi Etika Rini; Agus Santoso (Akademi Komunitas Perkebunan Yogyakarta, 2026)
The purpose of this study is 1) To identify the characteristics of respondents of coffee beverage products at Tilasawa Coffee Roaster. 2) To identify the average score of respondents' answers to the variables that affect consumer satisfaction of coffee beverage products at Tilasawa Coffee Roaster. 3) To analyze the effect of price, product quality and service quality on consumer satisfaction of coffee beverage products at Tilasawa Coffee Roaster. This study uses a quantitative approach with a descriptive research type, the determination of the location is determined by the purposive method and the method of selecting respondents using accidental sampling. The number of participants involved is 40 respondents. The data analysis technique used is descriptive analysis and multiple linear regression. The results of the study show that 1) The characteristics of respondents of coffee beverage products at Tilasawa Coffee Roaster are dominated by female gender, the age of respondents is dominated by 17-21 years old, the domicile or place of residence of respondents in this study is dominated by Yogyakarta, the last education of respondents is dominated by taking their last education at the high school level (SMA) and the occupation is dominated by students or college students. 2) The average score of respondents' answers on the price variable (X1), product quality variable (X2), service quality (X3) and consumer satisfaction (Y) are included in the satisfied category. 3) Price, product quality, and service quality have an individual and joint effect on consumer satisfaction of Tilasawa Coffee Roaster coffee beverage products.